(untitled) (Marketing Journal, 2026)
This article examines advanced international practices in managing the innovative development of the housing and коммун al services sector. Particular attention is paid to the experience of developed countries in digital transformation of utilities, impleme ntation of energy -saving technologies, development of smart infrastructure, and application of modern management mechanisms. The study substantiates contemporary approaches aimed at improving service quality, ensuring efficient resource utilization, and en hancing the sustainability of management systems in the housing and communal economy.